Differences in coping strategies in adult patients with bipolar disorder and their first-degree relatives in comparison to healthy controls - Bridi,Kelen Patrícia Bürke (2018)
Abstract Introduction: The objective of this study was to compare patients with bipolar disorder (BD), their first-degree relatives and a group of healthy controls in terms of use of adaptive and maladaptive coping strategies, exploring differences between specific types of strategies and their correlations with clinical variables. Methods: This was a cross-sectional study enrolling 36 euthymic patients with BD, 39 of their first-degree relatives and 44 controls. Coping strategies were assessed using the Brief COPE scale. Results: Significant differences were detected in the use of adaptive and maladaptive strategies by patients, their first-degree relatives and controls. Patients used adaptive strategies less often than the patients’ relatives (p<0.001) and controls (p = 0.003). There was no significant difference between first-degree relatives and controls (p=0.707). In contrast, patients (p<0.001) and their relatives (p=0.004) both exhibited higher scores for maladaptive coping than controls. There was no significant difference regarding the use of maladaptive strategies between patients and their relatives (p=0.517). Conclusions: First-degree relatives were at an intermediate level between patients with BD and controls regarding the use of coping skills. This finding supports the development of psychosocial interventions to encourage use of adaptive strategies rather than maladaptive strategies in this population.